The Use of Cutting-Stone-Slurry-Waste in Engineering Practice - Attom, Mousa (2010)
The paper studies the use of cutting stones-water-slurry-waste in engineering applications. Three types of selected clayey soils with different plasticity index and clay fraction were used. The initial physical properties of the clayey soils such as Atterberg’s limits, maximum dry density, optimum water content, specific gravity, and clay fraction were evaluated in accordance with American Standard for Testing and Materials (ASTM) standard specification. Cohesion, angle of internal friction and unconfined compressive strength were evaluated from samples remolded at 95% relative compaction and optimum water content. Two sets of soil samples were prepared for testing purpose in this investigation. The first set is prepared with fresh water at different initial water content and dry densities and without any admixture. The second set is identical to the first set but the water content is replaced with the same percentage of stones slurry waste (SSW). The two sets of samples were tested for the unconfined compressive strength at two different percentages of water content (first set) and cutting stones slurry (second set) and at three different initial dry densities. Additionally, the effect of mixing the soils with cutting stone slurry waste on the plastic index, dry densities and optimum water contents were studied. Results indicated that mixing the clay soil with cutting stone slurry waste increased the max dry density, and decreased the optimum water content percent and the plasticity index. Also, both unconfined compressive strength and the modulus of elasticity of the soil was improved significantly due to the addition of stone slurry waste to the tested soil.